Intelligent gender recognition system for classification of gender in Malaysian demographic - Su Chi, Yap; Syafiq Fauzi, Kamarulzaman (Universiti Malaysia Pahang, 2019)
Intelligent gender recognition is the ability in identify whether a person is a male or female based on the past experiences by the features of face such as eyes, mouth, cheek that makes the significant contribution to the appearance. Detecting human gender is difficult but important for some purposes, especially where safety issues related to female gender in public amenities is concerned. There were criminal cases that happened around the world concerning female gender in the public bathroom. The objectives of this research is to identify the techniques for classifying the different face features of male and female, embed as a system and validify using photos within Malaysian demographic. The scope of the project is focused on the face features for gender classification in real time, utilizing deep learning based gender recognition and HAAR Cascade classifier using pre-trained caffe model in OpenCV library to detect the gender.